THE INFLUENCE OF FINANCIAL STABILITY, NATURE OF INDUSTRY, CHANGE IN AUDITOR, CHANGE IN DIRECTOR ON FINANCIAL STATEMENT FRAUD WITH AUDIT COMMITTEE AS A MODERATION VARIABLE - Edi Supriyono; Evi Dyah Permata (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to determine the influence of Fraud Diamond Theory on financial statement fraud.This research uses a sample of manufacturing companies in the manufacture listed on the Indonesia Stock Exchange using the Purposive Sampling method. This research is quantitative research using primary data based on financial reports published by the Indonesian Stock Exchange. The sample in this study was 375. Hypothesis testing in this study used multiple regression analysis and MRA (Moderated Regression Analysis) through the EViews 12 application. Based on the results of the analysis carried out, it was found that (1) Financial stability had a positive effect on financial statement fraud, (2) Nature of industry had a positive effect on financial statement fraud, (3) Change in Auditor had a positive effect on financial statement fraud, (4) Change in director did not influence on financial statement fraud, (5) Audit committee is a non-moderating variable of financial stability on financial statement fraud, (6) Audit committee is a non-moderating variable of change in auditor on financial statement fraud. This research can provide insight as well as knowledge about how one financial statement fraud can be measured using the Beneish M Score formula. The results of this research can be used by companies to produce financial reports that are free from fraudulent practices and to identify patterns and methods of fraud that may occur. This allows for the implementation of effective preventive measures and increased supervision to reduce the risk of fraud in the future. The study focuses only on manufacturing companies listed on the Indonesian stock exchange for the period 2018-2022 and uses the Beneish M-score formula as a measure to detect fraudulent financial reporting.